Reformulasi Kebijakan Legalisasi Ganja untuk Kepentingan Medis: Tinjauan Hukum Pidana - Lestari, Dewi Ayu (SIGn Jurnal Hukum, 2024)
This research examines the imperative for reforming cannabis legalization policies in Indonesia, specifically for medical purposes, from both juridical and criminal law perspectives. Employing a normative legal research methodology with a tripartite approach encompassing statutory analysis, comparative jurisprudence, and case study examination, this study critically analyzes the current legal framework governing cannabis in Indonesia and its juxtaposition with international trends. Findings reveal that while medical cannabis legalization is gaining momentum globally, demonstrating positive impacts on patient health, public health, and economic development, Indonesia’s regulatory approach remains mired in ambiguity and inconsistency. This dissonance stems from a conflict between the restrictive provisions of Law Number 35 of 2009 and the growing body of scientific evidence supporting the therapeutic potential of cannabis in treating various conditions, including autism spectrum disorder, epilepsy, Tourette syndrome, and multiple sclerosis. This research argues for a more humane and progressive policy framework that aligns with scientific advancements and prioritizes public health. It proposes two primary pathways for reform: judicial review challenging the constitutionality of existing prohibitive legislation and legislative amendments to Law Number 35 of 2009. Crucially, any reform effort must be grounded in rigorous scientific evidence and accompanied by the development of comprehensive regulatory protocols and public education campaigns to ensure the safe and responsible use of medical cannabis. This research critically analyses the legal and policy landscape surrounding medical cannabis in Indonesia, offering evidence-based recommendations to guide policymakers towards a more just and effective regulatory framework.